Pengaruh Teknologi Informasi dan Komunikasi (TIK) Terhadap Ketimpangan Pendapatan di Indonesia - Fauziah Adlina M; Yollit Permata Sari (Media Riset Ekonomi Pembangunan (MedREP), 2025)
This study aims to analyze and identify the influence of the Information and Communication Technology Development Index (IP-ICT) on income inequality in Indonesia. This study uses panel data from 34 provinces during the period 2015-2023. The analysis method used is beta regression. The results of the analysis show that ICT Development Index has a positive and significant effect on income inequality. These findings provide an illustration that ICT Development Index will drive income inequality up. Because non-inclusive ICT development can strengthen the dominance of certain groups in accessing digital-based economic opportunities, the government needs to design affirmative policies to ensure that the benefits of digital transformation can be enjoyed equally by all levels of society.